Effect of Group Activity Therapy (TAK) Progressive Muscle Relaxation on Pain Scale and Mental Health in the Elderly: Pengaruh Terapi Aktivitas Kelompok (TAK) Relaksasi Otot Progresif Terhadap Nyeri dan Kesehatan Mental Lansia - Laras Ati, Niken Asih; Zahro , Siti Fatimatus; Pusparini, Yeni; Widowati , Sekar Ayu; Rofi’ah , Siti Nur (Jurnal Kesehatan Komunitas Indonesia, 2022)
The Elderly is a risk group prone to physical and psychological changes. Physical and psychological changes in the elderly cause disturbances in daily activities. The physical and mental health of the elderly are two things that have a reciprocal relationship that requires pharmacological and non-pharmacological treatment. This study aims to examine the effect of progressive muscle relaxation therapy on physical health (pain) and mental health (stress, anxiety, and depression) in the elderly. This research is Quasi-Experimental research using a one-group pre-post test design approach. The population in this study were all elderly living in the homestead at the Tresna Wredha Social Institution in the Jember Region. The Numerical Rating Scale for pain and DASS-21 measures pain, stress, anxiety, and depression in the elderly before and after implementing progressive muscle relaxation therapy. The results of this study showed that there were significant differences between before and after administration of progressive muscle relaxation therapy for pain (p-value = 0.000), stress (p-value = 0.000), anxiety (p-value = 0.000), and depression (p-value =0.000) in the elderly. The results of this study are expected to be the basis for implementing progressive muscle relaxation therapy to reduce pain, stress, anxiety, and depression in the elderly so that it is expected that the physical and psychological health of the elderly can improve.